Anaerobic co-digestion of grass and forbs – Influence of cattle manure or grass based inoculum. (December 2018) - Cong, Wen-Feng; Moset, Veronica; Feng, Lu; Møller, Henrik Bjarne; Eriksen, Jørgen
Abstract: Anaerobic co-digestion of agricultural by-products or wastes with complementarity characteristics is commonly used to enhance methane yield. This study firstly explores the possibility of co-digesting grass and forb species (white clover, chicory and plantain) differing in nutrient composition in enhancing methane yield. This was examined with two inocula (a cattle manure-based inoculum and a grass-based inoculum) in a batch assay. Results showed that co-digesting grass and forbs synergistically enhanced methane yield potential on average by 31 L kg −1 volatile solids (+11%) and reduced lag phase time by 0.8 day in the grass-based inoculum, but not in the cattle manure-based inoculum. Mixtures containing plantain showed more consistent synergistic effect than chicory. Synergistic effects were attributed to more balanced nutrient composition (especially C/N ratio) in grass-forb mixtures. We demonstrate that anaerobic co-digestion of grass and forbs is feasible for enhancing methane yield, which promotes the utilization of multi-species grasslands for bioenergy production. Highlights: Co-digestion of grass and forbs was examined with two inocula in a batch assay. Co-digestion enhanced bio-methane potential in grass-based inoculum. Co-digestion reduced the lag phase time in grass-based inoculum. Synergistic effect was attributed to better nutrient balance in grass-forb mixtures. No effect of co-digestion occurred in cattle manure-based inoculum.